The Effect of Bio Liquid Fertilizer Application on The Growth and Yield of Two Varieties of Maize (Zea mays L.) - Zikril Maulana; Zaitun Zaitun; Jumini Jumini (Syiah Kuala University, 2015)
The research was conducted at the experimental field of Assessment Institute for Agricultural Technology (BPTP) Lampineung Banda Aceh. The experimental arranged in a randomized complate block design in a factorial design with three replications. Bio liquid fertilizer Ultra Gen consisted of four levels, i.e. without liquid fertilizer (P0), 0,8 liter ha-1 (P1), 1,7 liter ha-1 (P2), and 2,5 liter ha-1 (P3). Varieties consisted of two levels, i.e. Pertiwi (V1) and Local Aceh (V2). Parameters observed in this research were plant height and number of leaves aged 15, 30, and 45 days after planting, corn length with cornhusk and without cornhusk, corn diameter with cornhusk and without cornhusk, corn weight with cornhusk and without cornhusk, weight of 100 grain dry seeds, shelled seeds weight dry per plant and yield. The result showed that concentration of 0.8 liter ha-1 gives better results compared to concentrations of other bio liquid fertilizer Ultra Gen, and Local Aceh variety of maize crop is better compared to Pertiwi variety